1986
DOI: 10.1177/0148607186010003322
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Oral Phenytoin with Enteral Feedings

Abstract: A 48-yr-old man with squamous cell carcinoma of the lung, hypercalcemia, and brain metastases with seizures was treated with phenytoin. Constant nasogastric infusion with Osmolyte was begun for hydration and nutritional status, necessitating an increase in his phenytoin dosage. Adequate seizure control and phenytoin levels were obtained on this adjusted regimen. However, on the 16th hospital day, the patient pulled out his nasogastric tube and received two doses of phenytoin without Osmolyte. The patient becam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Bauer reported a 70% to 80% decrease in serum phenytoin concentrations when phenytoin suspension was administered by nasogastric tube concurrently with a continuous tube feeding of Isocal 2 . The absorption of phenytoin has also been found to be decreased by Osmolite and vanilla pudding 3–6 . In our case, retrospective analysis revealed that phenytoin sodium capsules were coadministered with Ensure at bedtime.…”
Section: Commentsmentioning
confidence: 57%
“…Bauer reported a 70% to 80% decrease in serum phenytoin concentrations when phenytoin suspension was administered by nasogastric tube concurrently with a continuous tube feeding of Isocal 2 . The absorption of phenytoin has also been found to be decreased by Osmolite and vanilla pudding 3–6 . In our case, retrospective analysis revealed that phenytoin sodium capsules were coadministered with Ensure at bedtime.…”
Section: Commentsmentioning
confidence: 57%
“…Of the 29 patients observed, 15 (52%) were fitted with a nasogastric tube, ten (34%) with a percutaneous endoscopic gastrostomy and four (14%) with a jejunostomy. The average number of drugs was 6.5 per patient (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Analgesics represented 16% of all drugs administered in this manner and antipsychotics 13%.…”
Section: Introductionmentioning
confidence: 99%
“…A number of in vitro and in vivo studies as well as case reports have led to contradictory conclusions for all three of these drugs [5][6][7][8][9][10][11][12][13]. A literature review published in 2000 [14] concluded that phenytoin administration by nasogastric tube led to decreased absorption and lower than expected plasma concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…z Administering medications or nutrient solutions can clog tubes, with the incidence varying from 2% to 9%. 1 The preferred method for tube feeding in hospital is a continuous drip over [12][13][14][15][16][17][18][19][20][21][22][23][24] hours, usually by an infusion pump, as it reduces complications such as pulmonary aspiration and diarrhoea. If continuous drip feedings have been well tolerated, then bolus feeds can be used as long as the feeding tube is placed in the stomach -the stomach acts as a reservoir and delivers tolerable amounts of formula to the intestines.…”
Section: Introductionmentioning
confidence: 99%